2008
DOI: 10.1007/s00432-008-0352-z
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 expression links to malignant potential of cervical squamous cell carcinoma

Abstract: The present results suggest that decreased Gal-9 expression is inversely associated with malignant potential or differentiation of cervical CIN and SCC as a differentiation biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 29 publications
6
49
2
Order By: Relevance
“…Friedrichs et al (2007) reported that galectin-3 and-9 are the most abundantly expressed galectins in Madin-Darby canine kidney (MDCK) cells, a commonly used general model for epithelial cells, which comprise epithelium. Liang et al (2008) observed potent immunostaining for cytoplasmic Galectin-9 in normal squamous epithelial cells of the cervix which appears to involve the entire epithelium while Cada et al (2009) reported basal and suprabasal presence of Galectin-9 in the epidermis. More relevantly, Fik et al (2013) described expression of Galectin-9 exclusively at the basal layer of normal oral epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Friedrichs et al (2007) reported that galectin-3 and-9 are the most abundantly expressed galectins in Madin-Darby canine kidney (MDCK) cells, a commonly used general model for epithelial cells, which comprise epithelium. Liang et al (2008) observed potent immunostaining for cytoplasmic Galectin-9 in normal squamous epithelial cells of the cervix which appears to involve the entire epithelium while Cada et al (2009) reported basal and suprabasal presence of Galectin-9 in the epidermis. More relevantly, Fik et al (2013) described expression of Galectin-9 exclusively at the basal layer of normal oral epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…H-SCORE is a summation of the proportion of cell staining at each intensity multiplied by the intensity of the staining (Berchuck et al, 1989) represented by the following formula (Kitawaki et al, 1999;Liang et al, 2008):…”
Section: Ihc Staining Evaluationmentioning
confidence: 99%
“…12,13 Loss of expression of LGALS9 is also associated with metastatic progression in various epithelial cancers, including breast and colorectal cancer. [14][15][16][17][18] Taken together, this suggests that loss of LGALS9 promotes a metastatic tumor phenotype. Conversely, treatment of LGALS9 deficient monolayers with exogenous recombinant LGALS9 (rLGALS9) restores epithelial polarity.…”
Section: Introductionmentioning
confidence: 88%
“…For example, studies have shown interaction between the gal-9 on lymphocytes and the Tim-3 on APCs may have a positive role in DC maturation process, 13,22 while ligation of the gal-9 on APCs and the Tim-3 on lymphocytes have an opposite role as to tune down the immune response. 15,35,36,46,49 The function of the various gal-9 ϩ immuneregulatory cells seen in mice with advanced AML on the generation and function of CD8 ϩ T cells in this model is of interest and will require extensive future investigations beyond the scope of this study to clearly define the role of each.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown interaction between the gal-9 on lymphocytes and the Tim-3 on APCs may have a positive role in DC maturation process, 13,22 while ligation of the gal-9 on APCs and the Tim-3 on lymphocytes have an opposite role as to tune down the immune response. 15,35,36,46,49 The function of the various gal-9 ϩ immuneregulatory cells seen in mice with advanced AML on the generation and function of CD8 ϩ T cells in this model is of interest and will require extensive future investigations beyond the scope of this study to clearly define the role of each.The additive effects of combined in vivo blockade of the PD-1/PDL1 and Tim-3/gal-9 in reducing AML disease burden and prolonging survival was demonstrated in studies in which Tim3-Fc fusion protein and anti-PDL1 mAb were given to WT mice or anti-PDL1 mAb was given to gal-9 KO mice. The latter resulted in a more pronounced long-term survival than the former, which may be because of the incomplete blockade at sites of AML disease likely achieved with a fusion protein compared with the obligatory blockade of a KO mouse.…”
mentioning
confidence: 99%